Use of whey protein nanoparticles for the encapsulation and sustained delivery of beta-carotene and zinc micronutrient - Salem, Alshaimaa (AUC Knowledge Fountain, 2015)
Nanoparticles prepared from whey protein isolates can be used for encapsulation and sustained delivery of β-carotene and zinc (II) ions. The loaded whey protein nanoparticles were prepared by the pH cycle method at aggregation pH 6 and 22 h ageing time in the presence of calcium ions. Morphology, particle size, stability and release profiles at neutral and acidic conditions of the loaded whey protein nanoparticles were evaluated. The results illustrated that whey protein nanoparticles were able to encapsulate β-carotene molecules in spherical compact structuresof around 400 nm that can protect sensitive β-carotene and limit its susceptibility to auto-oxidation reactions when compared to control samples. Moreover, Whey protein nanoparticles showed higher release profiles at neutral conditions compared to acidic conditions even in the presence of proteo-lytic enzymes. These findings confirmed that whey protein nanoparticles can be used to encapsulate, protect and enhance the release profile of sensitive biological active ingredients and micronutrients to be used for food as well as pharmaceutical applications.